2021
DOI: 10.1021/acs.est.1c03804
|View full text |Cite
|
Sign up to set email alerts
|

Radical-Driven Decomposition of Graphitic Carbon Nitride Nanosheets: Light Exposure Matters

Abstract: Understanding the transformation of graphitic carbon nitride (g-C3N4) is essential to assess nanomaterial robustness and environmental risks. Using an integrated experimental and simulation approach, our work has demonstrated that the photoinduced hole (h+) on g-C3N4 nanosheets significantly enhances nanomaterial decomposition under •OH attack. Two g-C3N4 nanosheet samples D and M2 were synthesized, among which M2 had more pores, defects, and edges, and they were subjected to treatments with •OH alone and both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 62 publications
1
23
1
Order By: Relevance
“…C 3 N 4 -based materials normally lack chemical stability in catalytic oxidation reactions because the highly oxidative ROS will destroy the heptazine units of C 3 N 4 . , In Figure S34a,b, the as-synthesized WUCN-500 demonstrated good recyclability in photocatalytic ozonation. Compared with the previously reported g-C 3 N 4 -driven photocatalytic ozonation system, the solar/O 3 /WUCN-500 system resulted in a decreased level of dissolved TOC without the presence of the organic pollutants (Figure S34c).…”
Section: Resultsmentioning
confidence: 99%
“…C 3 N 4 -based materials normally lack chemical stability in catalytic oxidation reactions because the highly oxidative ROS will destroy the heptazine units of C 3 N 4 . , In Figure S34a,b, the as-synthesized WUCN-500 demonstrated good recyclability in photocatalytic ozonation. Compared with the previously reported g-C 3 N 4 -driven photocatalytic ozonation system, the solar/O 3 /WUCN-500 system resulted in a decreased level of dissolved TOC without the presence of the organic pollutants (Figure S34c).…”
Section: Resultsmentioning
confidence: 99%
“…When using both pure and modified g-C 3 N 4 for CO 2 photoreduction, the main reported products are carbon monoxide (CO) and/or methane (CH 4 ) in the gas–solid system and methanol (CH 3 OH), ethanol (C 2 H 5 OH), and formic acid (HCOOH) in the liquid–solid system. However, the reaction rates are generally very low, typically in the micromolar per gram per hour range. Generally, g-C 3 N 4 has been considered to have excellent chemical and thermal stabilities, which is reflected by its relatively stable activity during cyclic use. ,, However, recent studies have demonstrated the instability of g-C 3 N 4 under actual working conditions. In fact, g-C 3 N 4 has been shown to be oxidized and release nitrate and soluble organic fragments as a result of an attack by photo-induced holes (h + ) and • OH radicals in the aqueous phase . Additionally, Xiao et al also showed that g-C 3 N 4 is decomposed into nitrates in the aqueous environment by ozone-derived hydroxyl radicals ( • OH) .…”
Section: Introductionmentioning
confidence: 99%
“…18−21 In fact, g-C 3 N 4 has been shown to be oxidized and release nitrate and soluble organic fragments as a result of an attack by photo-induced holes (h + ) and • OH radicals in the aqueous phase. 18 Additionally, Xiao et al also showed that g-C 3 N 4 is decomposed into nitrates in the aqueous environment by ozone-derived hydroxyl radicals ( • OH). 19 The selfdecomposition pathways of g-C 3 N 4 have also been found to involve superoxide ( • O 2 − ) radicals and holes (h + ).…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the field of catalysis, single-atom catalysts (SACs) have attracted much interest due to their high performance for various important reactions including hydrogen evolution reaction, carbon dioxide reduction reaction, photocatalytic synthesis of hydrogen peroxide (H 2 O 2 ), and electrochemical H 2 O 2 production using carbon-material-based SAC electrodes. While the SACs can exhibit extremely high efficiency and selectivity like the enzymes in the biological systems, the activity is susceptible to deterioration over time because the existence of catalytically active sites is usually limited to the surface. Particularly, carbon-based materials are known to undergo deterioration under harsh conditions in the oxygen reduction reaction (ORR) and water oxidation reaction (WOR). On the other hand, doping of antimony into semiconducting SnO 2 with a band gap of ∼3.6 eV (SnO 2 :Sb) induces high electric conductivity with the high transparency in the visible region maintained. Due to the unique properties in addition to the extraordinary robustness, SnO 2 :Sb is widely applied to the electrodes for solar cells, photoelectrochemical cells, and solid-state sensors. Meanwhile, the application of SnO 2 :Sb to chemistry has not been very widespread so far.…”
Section: Introductionmentioning
confidence: 99%